Thymoquinone’s Antiviral Effects: It is Time to be Proven in the Covid-19 Pandemic Era and its Omicron Variant Surge - Abdelrahim, Maen; Esmail, Abdullah; Al Saadi, Noor; Zsigmond, Eva; Al Najjar, Ebtesam; Bugazia, Doaa; Al-Rawi, Hadeel; Alsaadi, Ayat; Kaseb, Ahmed O. (Frontiers in Pharmacology, 2022)
The COVID-19 pandemic has impacted every country in the world. With more than 400 million cases and more than 5.5 million deaths. The FDA either approved or authorized the emergency use for three vaccines against COVID-19. The treatment options of COVID-19 are very limited. Multiple complementary and alternative medicine modalities were suggested to be efficacious in the treatment of COVID-19 such as Thymoquinone. The effects of Thymoquinone have been examined and multiple studies indicate a promising beneficial effect. However, the current body of research is limited in terms of its scope, quality, and quantity. While higher-quality studies are required, physicians do not routinely recommend the use of marketed supplements of natural products, including Thymoquinone for COVID-19. Given the numerous suggested positive effects of Thymoquinone, including anti-inflammatory and antimicrobial properties, additional research is required to confirm or refute these promising benefits. Complementary and alternative medicine is an area that requires additional evidence-based practice and research to confirm effects observed in clinical practice.